THE IRREVERSIBLE DAMAGE OF BODY SHAMING ON THE IDENTITY OF SOUTH AFRICAN WOMEN ON SOCIAL MEDIA - Mmathato Calphurnia RAMMUTLA (Social Sciences and Education Research Review)
This systematic review explores the irreversible damage of body shaming on the identity of South African women on social media. Many people use social media, and women who use it are exposed to a variety of media users from all walks of life. As a result, when they post about themselves on these platforms, they receive a range of responses, from compliments to body shaming, which seems to be particularly popular among South African women. These women receive criticism and judgment based on their body types, which are contrasted with social media's standards. Two conceptual frameworks namely, Black feminist and Self-objectification theories provided perspectives about social media influence on the body shaming of South African women. Google scholar, Taylor and Francis, Scopus and ResearchGate were used to retrieve and analyse data from twenty-two (22) peer-reviewed journal articles (n=22) published between 2015 and 2023. Recommendations are also provided to help with further exploration to the impact of social media on South African women's body shaming. Therefore, the study is profitable as it paves the way for further studies relating to the research topic within the South African context.